Checklist para rastreamento das dificuldades no manuseio do auxiliar auditivo por idosos - Lima, Annacarla Carvalho Alves de (2018)
Introduction: Presbycusis consists of the process of natural deterioration and wear of structures related to human hearing. It needs intervention to subside its effects, because it is characterized as a progressive and irreversible process. There is no curative, but only rehabilitative treatment. Through the use of hearing aids, it is possible to reduce the sensory organ gap, improving its functionality. However the process of use and adaptation requires a lot of care and assistance to be successful. And, despite the technological progress that increasingly qualifies these electronic amplification devices to meet all needs, it is observed that the prevalence of the elderly who reject or are maladapted is high. Objectives: 1. To identify in the literature the difficulties encountered in the use of hearing aid by the elderly; 2. To elaborate a checklist (product) to track the difficulties of the elderly in the handling of the hearing aid; 3. Validate the checklist (product) that will serve to track the difficulties of the elderly in the handling of the hearing . Method: This is a methodological study of quantitative approach. The research was carried out in a hospital that provides hearing aids through the Auditory High Complexity Procedure (AHCP) program in João Pessoa - PB and in private clinics that perform indication and adaptation of hearing aid. The sample consisted of 20 elderly people who accepted to participate in the study, primary users of hearing aids who were performing their first return to the SUS service and 9 Speech Therapists specializing in Audiology and hearing aids for at least one year. The instruments used were a questionnaire, containing 15 questions about the manipulation of the device, answered by the elderly and a checklist made by the specialists evaluating the instrument constructed to recognize the obstacles in the handling of the auditory amplification resource. The analyzes of the results were performed through descriptive statistics. The project was submitted to the Research Ethics Committee of the Health Sciences Center of the Federal University of Paraíba and approved on July 27, 2017, under the CAAE; 67103917.6.0000.5188. Results and Discussion: From this study two articles were originated: the first one related to literature review, which identified the difficulties faced by the elderly to use the auditory amplification resource. The obstacles came from various sources, preponderating the lack of the orientation / monitoring / handling phase, mainly for the elderly that are served in the public network. The second article (the original one) gave subsidies for the elaboration of a checklist in order to identify the difficulties of the elderly to manipulate the amplification device. Conclusions: Through the analysis of the literature, it was possible to identify the main reasons that cause difficulties in the use of the hearing aid by the elderly. Some of these barriers were confirmed with the elderly users of hearing aids, through the application of the questionnaire; these findings generated an instrument whose goal is to track the obstacles experienced by the elderly in the acclimatization phase so that the Speech-Language Pathologist can guide them and thus reduce or eliminate these difficulties.